PENGARUH SALES PROMOTION DAN BRAND EXPERIENCE DALAM MEMBANGUN CUSTOMER E-SATISFACTION PENGGUNA DANA DI KOTA BANDUNG - Linggani Candra Kirana; Raka Pradana Virzi; Kevin Alwino Tunasrluzon Busyra (ITB AAS INDONESIA Surakarta, 2021)
This research aims to determine (1) the partial influence of sales promotion on the development of customer e-satisfaction, (2) the partial influence of brand experience on the development of customer e-satisfaction, as well as (3) the influence of sales promotion and brand experience simultaneously on the development of DANA customer e-satisfaction in Bandung City. Sales Promotion and Brand Experience are two factors that can influence the development of Customer E-Satisfaction. This research was conducted by distributing questionnaires to 100 respondents who are DANA app users, domicile in Bandung City. Researcher was using quantitative method with correlation analysis and multiple linear regression techniques, while for the hypothesis testing researcher was using coefficient of determination test (R2), T test and F test. The results show that there are a partial and simultaneous influences between Sales Promotion and Brand Experience on the development Customer E-satisfaction. Keywords : Sales Promotion, Brand Experience, Customer E-satisfaction.